(untitled) (Texas Journal of Engineering and Technology, 2023)
In order to operate a wind turbine generator, careful and extensive research is required as different environmental conditions result in different wind speeds. Standard type of induction generators and compatible electric generators are great in the construction of low-speed applications. Due to the improved architecture and lower PM material emissions, a permanent magnet generator is an ideal choice for low-speed direct applications. Different topology of permanent magnet generator are available, such as radial flux, axial flux, and transverse flux PMG. The sophisticated structure of the permanent axial flux generator is not suitable for use in large wind turbines. Due to the simple structure of radial flux PMG, the formation of multiple poles can be easily incorporated into the nascalle of wind turbines. To overcome these obstacles, this research project proposes a new topology quasi-Z-source Matrix converter-based DC / DC using a zigzag transformer, and simulation is performed and compared with other existing DC-based Z-source converters. DC will be approved at the beginning of the power supply unit in DC power supply systems